An Improved Needleman-Wunsch Algorithm for Pairwise Sequence Alignment of Protein-Albumin - Muflikhah, Lailil; Eka R., Dian (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper aims to improve the method of optimal global sequence alignment in order to increase the computational performance. The huge number of genome sequences is main problem of alignment. One of global sequence alignment methods is Needleman-Wunsch algorithm. This algorithm is implemented by constructing a MxN matrix, which M is the length of first sequence and N is the length of second sequence. All cells of the matrix are filled to compute the score for constructing global pairwise sequence alignment, so that the time and space complexity are very high. Therefore, the improved Needleman-Wunsch algorithm (INWA) is addressed to compute partially for the score in the cells. The test set consisted of 1250 pairwise sequence alignments of human protein-albumin and it is compared to the original method. As a result shows that the space and time compexity of INWA is O(N) instead of O(MN).